Does the use of riparian buffer zones in forest drainage sites to reduce the transport of solids simultaneously increase the export of solutes? - Nieminen, M.; Ahti, E.; Nousiainen, H.; Joensuu, S.; Vuollekoski, M. (Boreal Environment Research Publishing Board, 2024)
Riparian buffer zone areas (BZAs) effectively reduce sediment transport and are considered as the most important water protection method in forest drainage sites in Finland. However, it has been questioned whether BZAs are a significant source of nutrients and other dissolved constituents to water-courses. At seven locations in south-central Finland a buffer zone was created below a drainage site and the effects on the concentrations of dissolved organic carbon (DOC), dissolved P, Fe and Al in through-flow were studied for 4–7 years. The effect of the two smallest BZAs (%X 0.1% of watershed area) on through-flow quality was negligible. The three medium-sized BZAs (0.15%–0.23% of watershed area) either had no effect on through-flow quality or slightly increased solute concentrations (3%–30%). At the two largest BZAs (> 1% of watershed area) the concentrations of Fe either increased or decreased and the concentrations of DOC, Al and P were either unaffected or decreased (15%–27%). It was concluded that, although increased leaching may occur from some individual sites, BZAs are unlikely to act as a general source of P, Al, Fe, or DOC to water courses.